The impact of transcendental leadership in enhancing university performance (Field research) - خضير, ليلى عبد الله; العامري, فراس محمد (Journal of Economics and Administrative Sciences, 2020)
Current research aims to analyze the relationship and impact of the explanatory variable transcendental leadership, which includes dimensions (values ​​and attitudes, behavior, spirituality, vision and hope/faith) in the responsive variable university performance dimensions (relationships and resources available, human capital development, scientific research, community service). Field research for the leaders of a number of colleges of the University of Baghdad of the deans of the colleges of research and assistants of deans and heads of departments, the main research problem was the important question (what is the role of transcendent leadership in promoting university performance) and the research started from two main hypotheses for the purpose of clarifying the relationship of influence and For the correlation between research variables, the questionnaire was used as the main tool for collecting and analyzing data. The answers of the research sample were analyzed which included (104) respondents representing the research sample exclusively and comprehensively. Interviews were used as well as field observations through the field presence of the researcher. The statistical program (SPSS_V.20) was used with the adoption of a set of statistical methods such as (mean, percentages, repetition, standard deviation, coefficient of variation, relative importance, Spearman correlation, and simple linear regression equation). The research is based on the results obtained, including the lack of financial resources available to the colleges of the respondents to cover their expenses, as well as transcendent leadership directly affect the enhancement of university performance in the population of Baghdad University and its research colleges. This influence is increased and is exacerbated by behavior, vision, hope/faith, values, trends, and spirituality.